THE EFFECT OF THINK PAIR SHARE TECHNIQUE ON THE ENGLISH READING ACHIEVEMENT OF THE STUDENTS DIFFERING IN ACHIEVEMENT MOTIVATION AT GRADE EIGHT OF SMPN 13 MATARAM - ., M. AFAN; ., Prof. Dr. A. A. I. Ngurah Marhaeni,MA; ., Prof. Dr. Nyoman Dantes (Jurnal Pendidikan Bahasa Inggris, 2013)
This experimental research aimed at finding out the effect of Think-Pair-Share technique on the English reading achievement of the Students differing in achievement motivation at grade eight of SMPN 13 Mataram. This research with posttest only control group design by using 2x2 factorial design. The instrument used in this research are, English reading achievement test and achievement motivation questionnaire. 80 students were taken from six regular classes as the research sample with cluster random sampling technique. than divided them into experimental group and control group The obtained data were analyzed by administering quantitative descriptive analysis with two ways analysis of variant (ANOVA). From the result of analysis it can be concluded that; 1). There was a significant difference in English reading achievement between the groups of student who were taught by using think-pair-share technique and those taught with conventional teaching technique. 2). There was an interaction effect between the teaching technique and achievement motivation toward the English reading achievement of the students. 3). There was a significant difference in English reading achievement between the group of students who had high achievement motivation taught with think-pair share cooperative technique and those who were taught with conventional teaching technique. 4) There was no significant difference in English reading achievement between the group of students who had low achievement motivation taught with think-pair share cooperative technique and those who were taught with conventional teaching technique. keyword : Think-Pair-Share Teaching Technique, English Reading Achievement, Achievement Motivation.